Old New Orleans - Muse, Vance (Birmingham, AL Oxmoor House, Inc., 1988)
D., 8/99
Keywords: New Orleans (LA.)--Dweelings; Historic buildings--Louisiana--New Orleans; Electicism in architecture--Louisiana--New Orleans